Preparation method and application of high-performance NiW alloy methanation catalyst

The NiW alloy methanation catalyst addresses deactivation and performance issues by enhancing carrier surface area and alloying, achieving improved CO conversion and methane selectivity with sustained activity.

CN119114093APending Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311520654.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2023-11-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing methanation catalysts face issues such as easy deactivation, low CO conversion rate, and poor methane selectivity, with traditional nickel-based catalysts having reduced active sites and stability concerns.

Method used

A method for preparing a NiW alloy methanation catalyst using a surfactant to increase the carrier's specific surface area, combined with a co-precipitation method and co-impregnation of Ni-W bimetal, resulting in a high-performance catalyst with improved dispersion and alloy effect.

Benefits of technology

The NiW alloy catalyst exhibits enhanced activity, selectivity, and stability, maintaining good performance over extended periods, with stable alloy structure and minimal active component loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysis, and relates to a preparation method and application of a methanation catalyst. The preparation method comprises the following steps: adding a surfactant into a carrier emulsion through a synergistic effect of metals such as Mg, Zn, Ce and Zr to prepare a composite alumina carrier with a high specific surface area, and impregnating Ni and W double-active metals onto the carrier to obtain a catalyst finished product. The catalyst is composed of a carrier, an active component and an auxiliary agent, and the carrier accounts for 60-80%, the active component accounts for 10-15%, and the auxiliary agent accounts for 5-10% (based on the weight of the catalyst). The NiW alloy catalyst prepared by the method is simple in preparation method and beneficial to industrial production, and the problems that a traditional methanation catalyst is poor in stability, prone to poisoning and carbon deposition, low in CO and CO2 conversion rate and methane selectivity and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic technology, and specifically relates to a preparation method and application of a high-performance NiW alloy methanation catalyst. Background Art

[0002] As we all know, my country's energy resources are characterized by "rich in coal, poor in oil, and little gas". In recent years, my country's natural gas demand has continued to rise, and the supply gap has continued to increase. In order to ease the contradiction between natural gas supply and demand and increase the proportion of natural gas in my country's energy structure, the development of new, efficient and clean coal resource utilization technology and natural gas production process has good economic benefits and far-reaching social significance.

[0003] Methanation technology is the core technology for preparing natural gas from coke oven gas. Currently, the most widely used methanation catalyst in industry is supported nickel-based catalyst. Due to the high loading requirement of the catalyst, nickel nanoparticles are gathered on the surface of the carrier, which reduces the number of active sites and easily causes the loss of active components, thus reducing the activity of the catalyst. In addition, the catalyst also has the disadvantages of low CO conversion rate, poor methane selectivity, and difficulty in achieving a good balance between conversion rate and selectivity.

[0004] Chinese patent CN111686746A discloses a low-temperature methanation catalyst and its preparation method. The content of the active component of the catalyst accounts for 50% to 75% of the total mass of the catalyst, which will cause a large number of active components to accumulate on the surface of the carrier, which is easy to cause the reduction of active sites and the loss of active components. In addition, although the catalyst prepared by the patent shows good low-temperature activity, the activity and stability of the catalyst in long-term use are difficult to guarantee, and the stability of the catalyst is not mentioned in the patent.

[0005] The methanogenic catalyst provided by Chinese patent CN109046380A uses Ni as an active component, and after the introduction of stabilizer Au or Ag, there is an alloy effect and an electronic effect with Ni. Although the carbon deposition of the methane catalyst is greatly reduced and the stability is good, the CO conversion rate is average and the methane selectivity is low.

[0006] Therefore, it is necessary to develop a high-performance methanation catalyst. Summary of the invention

[0007] Purpose of the invention: The present invention provides a method for preparing a high-performance NiW alloy methanation catalyst, which solves the problems of easy deactivation of traditional methane synthesis catalysts, low CO conversion rate, and poor methane selectivity.

[0008] The main technical scheme of the present invention is: a method for preparing a NiW alloy methanation catalyst, which is characterized in that in the preparation of the catalyst, a surfactant is used to increase the specific surface area of ​​the carrier, and a modified oxide composite carrier with a high specific surface area is prepared by a co-precipitation method; Ni-W bimetal is used as an active component, and the NiW alloy methanation catalyst is prepared by a co-impregnation method.

[0009] The present invention provides a method for preparing a high-performance NiW alloy methanation catalyst, which is characterized in that the catalyst is obtained by the following steps: (1) Preparation of carrier: Dissolve the surfactant in deionized water, stir evenly to make it fully dissolved, control the temperature at 60-80°C, add aluminum nitrate and stir evenly; then add one or more of nitrates of Mg, Zn, Ce, and Zr, stir continuously for 2-4 hours, control the temperature between 60-80°C, add sodium carbonate solution to neutralize to obtain a carrier suspension, and control the pH value between 8-9; then filter the obtained material, wash, dry, press into tablets, and roast to obtain a carrier; (2) Preparation of active ingredients: Ni(NO3)2·6H2O and H3O 40 PW 12 Add to deionized water, add sodium carbonate solution, adjust the pH value to 4-5, and disperse by ultrasonic for 5 minutes to obtain the active component precursor liquid; (3) Preparation of catalyst: The composite carrier is supersaturatedly immersed in the precursor liquid for 2-4 hours, and the temperature of the immersion liquid is controlled at 80-90°C; the impregnated catalyst semi-finished product is taken out, and the catalyst finished product is obtained by drying and calcining.

[0010] The molar ratio of Al:X in the above steps is 1:(0.1-1.0), wherein X is one or more of Mg, Zn, Ce and Zr in step b.

[0011] In the above steps, the loading amounts of the active components Ni and W are 10-15 wt% and 5-10 wt% of the catalyst weight, respectively.

[0012] In the above steps, the active component W:Ni loading ratio is 1:(1.0~3.0).

[0013] In the above steps, the molar ratio of aluminum to surfactant is 1:(0.5~1.5).

[0014] In the above steps, the pH value of the carrier suspension is 8-9 and the temperature is 60-80°C.

[0015] In the above steps, the calcination temperature of the carrier is 400-600°C, and the calcination time is 4-6 h.

[0016] In the above steps, the pH of the active component precursor liquid is 4-5, and the temperature of the precursor liquid is 80-90°C.

[0017] In the above steps, the drying temperature of the catalyst semi-finished product is 100-120°C, and the drying time is 4-6 hours.

[0018] In the above steps, the calcination temperature of the catalyst semi-finished product is 400-600°C, and the calcination time is 4-6 h.

[0019] A typical laboratory preparation process of the present invention is as follows: 1) Dissolve 20-50 g of surfactant in 1 L of deionized water, stir well to make it fully dissolved, control the temperature at 60-80°C, add 100-150 g of aluminum nitrate and stir well; 2) Add 30-100 g of one or more of magnesium, zinc, cerium, and zirconium nitrates to the above solution, stir continuously for 2-4 hours, add 0.5-1.0 mol / L sodium carbonate solution for neutralization, and control the pH value at 8-9; 3) The obtained material is filtered, washed, dried, pressed into tablets, and then calcined in a muffle furnace at 400-600°C for 4-6 hours to obtain a composite carrier; 4) Ni(NO3)2·6H2O and H3O 40 PW 12 Add to deionized water, add sodium carbonate solution with a concentration of 0.5-1.0 mol / L, adjust the pH value to 4-5, and ultrasonically disperse for 5 minutes to obtain the active component precursor liquid; 5) Supersaturating the composite support into the precursor solution at a temperature of 80-90°C for 2-4 h; 6) After impregnation, the semi-finished catalyst is dried at 120°C for 6-8 h, and then calcined at 400-600°C for 4-6 h to obtain the finished catalyst.

[0020] The present invention provides an application of a NiW alloy catalyst prepared by the preparation method described in the above technical scheme in a methanation reaction, wherein the volume ratio of H2 to CO in the methanation reaction is 2:1.

[0021] The NiW alloy methanation catalyst prepared by the present invention has a simple preparation method and is conducive to industrial production; the carrier has a high specific area, which is conducive to the dispersion of active components, and the alloy effect between NiW makes the catalyst have good activity, selectivity and stability. Implementation

[0022] For further explanation, the present invention is described in detail by the following examples, but the present invention is not limited thereto. Example 1

[0023] 1) Dissolve 50 g of PVP in 1 L of deionized water, stir evenly to fully dissolve it, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 35 g of magnesium nitrate and 45 g of zinc nitrate to the above solution, stir continuously for 4 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.5; 3) Filter, wash, dry, press the obtained material into tablets, and calcine at 450°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Add 16.52 g of Ni(NO3)2·6H2O and 4.83 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.3, and ultrasonically disperse it for 5 min to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 4 h; 6) The impregnated catalyst semi-finished product is dried at 120°C for 6 h, and then calcined at 450°C for 4 h to obtain the catalyst finished product NW-1. Example 2

[0024] 1) Dissolve 20 g of PVA in 1 L of deionized water, stir evenly to make it fully dissolved, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 76.5 g of cerium nitrate and 80 g of zirconium nitrate to the above solution, stir continuously for 4 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.3; 3) Filter the obtained material, wash, dry, press into tablets, and calcine at 500°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Add 16.52 g of Ni(NO3)2·6H2O and 2.29 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.0, and ultrasonically disperse it for 5 min to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 4 h; 6) The impregnated catalyst semi-finished product is dried at 120°C for 6 h, and then calcined at 500°C for 4 h to obtain the catalyst finished product NW-2. Example 3

[0025] 1) Dissolve 145 g of DTAB in 1 L of deionized water, stir evenly to make it fully dissolved, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 35 g of magnesium nitrate and 76.5 g of cerium nitrate to the above solution, stir continuously for 4 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.6; 3) Filter the obtained material, wash, dry, press into tablets, and calcine at 550°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Mix 26.23 g of Ni(NO3)2·6H2O and 2.42 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.2, and ultrasonically disperse it for 5 minutes to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 4 hours; 6) The impregnated catalyst semi-finished product is dried at 110°C for 6 hours, and then calcined at 550°C for 4 hours to obtain the catalyst finished product NW-3. Example 4

[0026] 1) Dissolve 50 g of PVP in 1 L of deionized water, stir evenly to fully dissolve it, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 35 g of magnesium nitrate and 80 g of zirconium nitrate to the above solution, stir continuously for 2 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.4; 3) Filter the obtained material, wash, dry, press into tablets, and calcine at 600°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Add 16.52 g of Ni(NO3)2·6H2O and 4.83 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.5, and ultrasonically disperse it for 5 min to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 2 h; 6) The impregnated catalyst semi-finished product is dried at 110°C for 6 h, and then calcined at 600°C for 4 h to obtain the catalyst finished product NW-4. Example 5

[0027] 1) Dissolve 50 g of PVP in 1 L of deionized water, stir evenly to make it fully dissolved, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 80 g of zirconium nitrate to the above solution, stir continuously for 2 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.6; 3) Filter, wash, dry, press the obtained material into tablets, and calcine at 500°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Add 16.52 g of Ni(NO3)2·6H2O and 4.83 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.4, and ultrasonically disperse it for 5 min to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 4 hours; 6) The impregnated catalyst semi-finished product is dried at 100°C for 6 hours, and then calcined at 500°C for 4 hours to obtain the catalyst finished product NW-5. Example 6

[0028] 1) Dissolve 20 g of PVA in 1 L of deionized water, stir evenly to make it fully dissolved, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 76.5 g of cerium nitrate to the above solution, stir continuously for 3 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.4; 3) Filter the obtained material, wash, dry, press into tablets, and calcine at 500°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Add 16.52 g of Ni(NO3)2·6H2O and 4.83 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.2, and ultrasonically disperse it for 5 min to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 3 hours; 6) The impregnated catalyst semi-finished product is dried at 100°C for 7 hours, and then calcined at 500°C for 4 hours to obtain the catalyst finished product NW-6. Example 7

[0029] 1) Dissolve 20 g of PVA in 1 L of deionized water, stir evenly to make it fully dissolved, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 35 g of magnesium nitrate to the above solution, stir continuously for 3 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.7; 3) Filter, wash, dry, press the obtained material into tablets, and calcine at 550°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Mix 16.52 g of Ni(NO3)2·6H2O and 4.83 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.3, and ultrasonically disperse it for 5 minutes to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 4 hours; 6) The impregnated catalyst semi-finished product is dried at 120°C for 6 hours, and then calcined at 550°C for 4 hours to obtain the catalyst finished product NW-7. Example 8

[0030] 1) Dissolve 50 g of PVP in 1 L of deionized water, stir evenly to fully dissolve it, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 45 g of zinc nitrate to the above solution, stir continuously for 2 h, add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.3; 3) Filter the obtained material, wash, dry, press into tablets, and calcine at 500°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Mix 16.52 g of Ni(NO3)2·6H2O and 4.83 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.3, and ultrasonically disperse it for 5 min to obtain the active component precursor liquid; 5) At 85°C, supersaturate the composite carrier into the precursor liquid for 2 hours; 6) The impregnated catalyst semi-finished product is dried at 110°C for 6 hours, and then calcined at 500°C for 4 hours to obtain the catalyst finished product NW-8. Example 9

[0031] 1) Dissolve 20 g of PVA in 1 L of deionized water, stir evenly to make it fully dissolved, control the temperature at 70°C, add 100 g of aluminum nitrate and stir evenly; 2) Add 0.8 mol / L sodium carbonate solution for neutralization, and control the pH value at 8.6; 3) Filter, wash, dry, press the obtained material into tablets, and calcine at 600°C in a muffle furnace for 4 h to obtain a composite carrier; 4) Mix 16.52 g of Ni(NO3)2·6H2O and 4.83 g of H3O 40 PW 12 Add it into deionized water, add sodium carbonate solution with a concentration of 0.8 mol / L, adjust the pH value to 4.4, and ultrasonically disperse it for 5 min to obtain the active component precursor liquid; 5) At 85 °C, supersaturate the composite carrier into the precursor liquid for 2 h; 6) The impregnated catalyst semi-finished product is dried at 120 °C for 6 h, and then calcined at 600 °C for 4 h to obtain the catalyst finished product NW-9.

[0032] Comparative Example 1 The same as Example 1, the only difference is that the active component W is not added during the preparation of the catalyst, and the final catalyst D-1 is obtained.

[0033] Comparative Example 2 The method is the same as Example 2, except that during the preparation of the catalyst, the active components are changed to Ni and Mn, and finally catalyst D-2 is obtained.

[0034] Comparative Example 3 The same as Example 2, the only difference is that during the preparation of the catalyst, the calcination temperature of the carrier and the catalyst is changed to 300° C., and finally catalyst D-3 is obtained.

[0035] Catalyst performance evaluation Examples NW-1 to NW-9 and comparative examples D-1 to D-3 were loaded into a fixed bed tubular reactor, and the raw gas composition was: CO: 8%, CO2: 3%, H2: 52%, N2: 34.5%, C2H6: 2.5%. At a pressure of 2.0 MPa and a space velocity of 5000-10000 h -1 The performance test was carried out under the conditions of reaction temperature of 550℃, and samples were taken for analysis at 72 h and 500 h.

[0036] See Table 1 below for specific data.

[0037] Table 1 Comparison of catalyst performance between examples and comparative examples

[0038] It can be seen from the data in Table 1 that the catalyst prepared by this method can show good CO conversion rate and methane selectivity after 72 h and 500 h, especially the catalytic performance and stability of Examples 1 to 4 are good; while Comparative Example 1 does not add the active component W, resulting in low CO conversion rate and methane selectivity; although Comparative Examples 2 to 3 show good performance at 72 h, the conversion rate and selectivity are significantly reduced after 500 h of reaction, indicating that the catalyst has poor stability after long-term operation. At the same time, after the catalyst prepared by this method was removed after running for 500 h, it was found through chemical adsorption instrument testing that the active components of the catalyst formed a NiW alloy structure. Using ICP to analyze the metal element content of all catalysts, it was found that the metal element content of the catalyst in the embodiment did not change significantly, indicating that the alloy structure improves the stability of the catalyst; while the metal element content of the catalyst in the comparative example was greatly reduced compared to before the reaction, and the active component loss was serious.

Claims

1. A method for preparing a high-performance NiW alloy methanation catalyst, characterized in that The catalyst is obtained by the following steps: (1) Preparation of carrier: a. Dissolve the surfactant in deionized water, stir to fully dissolve, control the temperature at 60 ~ 80 ° C, add aluminum nitrate and stir; b. Add one or more nitrates of Mg, Zn, Ce, and Zr to step a, stir continuously for 2 to 4 h, and control the temperature between 60 and 80 ° C, add sodium carbonate solution for neutralization, and control the pH value between 8 and 9; c. The material obtained in step b is filtered, washed, dried, pressed into tablets, and calcined to obtain a carrier; (2) Preparation of active ingredients: d. Ni(NO3)2·6H2O and H3O 40 PW 12 Add to deionized water, add sodium carbonate solution, adjust the pH value to 4-5, and disperse by ultrasonic for 5 min to obtain the active component precursor liquid; (3) Preparation of catalyst: e. The composite support is supersaturatedly immersed in the precursor liquid for 2 to 4 h, and the temperature of the impregnation liquid is controlled between 80 and 90 ° C; the impregnated catalyst semi-finished product is taken out, and the catalyst product is obtained by drying and calcining.

2. The preparation method according to claim 1, characterized in that The loading amounts of active components Ni and W are 10~15wt% and 5~10 wt%, respectively.

3. The preparation method according to claim 1, characterized in that The active component W:Ni loading ratio is 1:(1.0~3.0).

4. The preparation method according to claim 1, characterized in that The molar ratio of Al:X is 1:(0.1-1.0), wherein X is one or more of Mg, Zn, Ce and Zr in step b.

5. The preparation method according to claim 1, characterized in that The surfactant in step a is one or more of polyvinyl pyrrolidone PVP, polyvinyl alcohol PVA, dodecyl trimethyl ammonium bromide DTAB, and sodium dodecyl sulfate SDS.

6. The preparation method according to claim 1, characterized in that In step a, the molar ratio of aluminum to surfactant is 1:(0.5-1.5).

7. The preparation method according to claim 1, characterized in that The molar concentration of sodium carbonate solution is 0.5~1.0 mol / L.

8. The preparation method according to claim 1, characterized in that In step c, the calcination temperature is 400-600° C. and the calcination time is 4-6 h.

9. The preparation method according to claim 1, characterized in that In step e, the drying temperature is 100-120° C. and the drying time is 4-6 h.

10. The preparation method according to claim 1, characterized in that In step e, the calcination temperature is 400-600° C. and the calcination time is 4-6 h.

11. Use of the NiW alloy catalyst prepared by the preparation method of the catalyst according to any one of claims 1 to 10 in a methanation reaction, wherein the volume ratio of H2 to CO in the methanation reaction is 2:1.